Development of a Mathematics Learning Management Model Emphasizing Authentic Assessment to Promote Executive Functions of Lower Secondary School Students - Sittiwong, Amornpan; Ngoenyuang, Sunee (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to 1) study the state of mathematics learning management emphasizing authentic assessment and the state of executive functions, and 2) develop a model and verify the quality of mathematics learning management emphasizing authentic assessment to promote executive functions of lower secondary school students in Chiang Rai province. The sample consisted of 411 lower secondary mathematics teachers in Chiang Rai province. The data were analyzed using descriptive statistics, Exploratory Factor Analysis (EFA), and Second-Order Confirmatory Factor Analysis (CFA). The research findings revealed that: (1) The state of mathematics learning management consisted of 9 factors, explaining 87.92% of the total variance. Meanwhile, the state of executive functions consisted of 7 factors, explaining 87.38% of the total variance. All indicators exhibited high factor loadings, indicating clear construct structures. (2) The verification of the structural model quality demonstrated that the learning management model fitted the empirical data perfectly χ² /df = 2.35, RMSEA = 0.057, CFI = 0.936, TLI = 0.931, SRMR = 0.070). Similarly, the executive function model indicated a good fit with the empirical data χ² /df = 2.65, RMSEA = 0.053, CFI = 0.942, TLI = 0.932, SRMR = 0.070). These findings confirmed the construct validity of the developed models and measurement tools, verifying their quality and suitability to be utilized as guidelines for instructional design to effectively enhance students’ executive functions.